Criação e implantação de estrutura de trabalho para melhorias de curto prazo em ambientes de compras públicas - Guizzardi, Erivelton (2014)
There are many researches that try to propose changes to the procedures for tendering and contracting, to improve the efficiency of public spending. However, studies that aim to understand and propose improvements in management process and operations and in the organizational environment of public purchasing are scarcer. The difficulties related to disorders or underperforming activities present in the environment of public procurement vary depending on various factors, such as the type of purchase, the team involved, the region, the government sphere, varying in function of time, since changes in laws and systems entail frequent changes in procedures. This study searched to purpose a framework that can be applied in distinct context and moments, aiming to achieve improvements in public purchasing environments. The application of the structure was made through the Research-Action approach, with the completion of a diagnostic to assess the environment, a analyze its dysfunctions and build a Current Reality Tree (CRT), followed by selection of short-term actions and projects and their implantation with the organization‟s own team, aiming to mitigate and eliminate dysfunctions to obtain improvements. The results indicate that the structure created allows implementing projects and short-term actions to optimize operations and processes involved, indicating lessons learned for efficient deployment.